Evanescent wave cavity ring-down spectroscopy in a thin-layer electrochemical cell. - Mazurenka, M; Wilkins, L; Macpherson, J; Unwin, P; Mackenzie, S (2006)
The application of evanescent wave cavity ring-down spectroscopy (EW-CRDS) in monitoring electrogenerated species within a thin-layer electrochemical cell is demonstrated. In the proof-of-concept experiments described, ferricyanide, Fe(CN)6(3-), was produced by the transport-limited oxidation of ferrocyanide, Fe(CN)6(4-), in a thin-layer solution cell (25-250 microm) formed between an electrode and the hypotenuse of a fused-silica prism. The prism constituted one element of a high-finesse optical cavity arranged in a triangular ring geometry with light being totally internally reflected at the silica/solution interface. The cavity was pumped with the output (approximately 417 nm) of a single-mode external cavity diode laser, which was continuously scanned across the cavity modes. The presence of electrogenerated ferricyanide within the resulting evanescent field, beyond the optical interface, was detected by the enhanced loss of light trapped within the cavity, as measured by the characteristic cavity ring down. In this way, the EW-CRDS technique is sensitive to absorption in only the first few hundred nanometers of solution above the silica surface. The cavity ring-down response accompanying both cyclic voltammetric and step potential chronoamperometry experiments at a variety of electrode-surface distances is presented, and the results are shown to be well reproduced in modeling by finite element methods. The studies herein thus provide a foundation for further applications of EW-CRDS combined with electrochemistry.